Comparative study on residents' perceptions of follow-up impacts of the 2008 Olympics. (December 2015) - Chen, Fangying; Tian, Lichao
Abstract: This study examines the perceptions of Chinese residents toward the impacts of the 2008 Olympics on their communities and compares the perceptions and attitudes of Beijing and Qingdao residents. These residents believe that the benefits and interests that they have gained from the event outweigh the costs, and that the intangible benefits outweigh the physical economic interests. The residents are divided into enthusiasts, realists, tolerators, and haters. Several differences are observed between the residents of the two cities. Beijing residents focus on environmental interests, whereas Qingdao residents focus on image. Beijing has a lower percentage of enthusiasts, but has a higher percentage of realists and haters than Qingdao. The implications of this study can be used by researchers and organizers of mega-events. Highlights: We examine Beijing and Qingdao residents' perceptions of the 2008 Olympics. Benefits and interests outweigh the costs. The intangible benefits outweigh the physical interests. For Qingdao residents, enthusiasts have a higher percentage. For Beijing residents, realists and haters have a higher percentage.